Metabolic and immune responses of Chinook salmon (Oncorhynchus tshawytscha) smolts to a short‐term poly (I:C) challenge. Issue 3 (23rd February 2020) - Lulijwa, Ronald; Alfaro, Andrea C.; Merien, Fabrice; Burdass, Mark; Meyer, Jill; Venter, Leonie; Young, Tim
Abstract: Polyinosinic:polycytidylic acid [poly (I:C)] was administered in vivo to Chinook salmon ( Oncorhynchus tshawytscha ) post‐smolts to determine the immune responses on haematological and cellular functional parameters, including spleen (SP), head kidney (HK) and red blood cell (RBC) cytokine expression, as well as serum metabolomics. Poly (I:C) in vivo (24 h exposure) did not affect fish haematological parameters, leucocyte phagocytic activity and phagocytic index, reactive oxygen species and nitric oxide production. Gas chromatography–mass spectrometry–based metabolomics revealed that poly (I:C) significantly altered the serum biochemistry profile of 25 metabolites. Metabolites involved in the branched‐chain amino acid/glutathione and transsulphuration pathways and phospholipid metabolism accumulated in poly (I:C)–treated fish, whereas those involved in the glycolytic and energy metabolism pathways were downregulated. At cytokine transcript level, poly (I:C) induced a significant upregulation of antiviral ifnγ in HK and Mx1 protein in HK, SP and RBCs. This study provides evidence for poly (I:C)–induced, immune‐related biomarkers at metabolic and molecular levels in farmed O. tshawytscha in vivo . These findings provide insights into short‐term effects of poly (I:C) at haematological, innate and adaptive immunity and metabolic levels, setting the stage for future studies.